Activity-regulated cytoskeleton-associated protein/activity-regulated gene 3.1 (Arc/Arg3.1) enhances dendritic cell vaccination in experimental melanoma. (1st January 2021) - Zhang, Xin-Wen; Huck, Katrin; Jähne, Kristine; Cichon, Frederik; Sonner, Jana K.; Ufer, Friederike; Bauer, Simone; Woo, Marcel Seungsu; Green, Ed; Lu, Kevin; Kilian, Michael; Friese, Manuel A.; et al.
ABSTRACT: Dendritic cell (DC) vaccination has proven to be an effective and safe adjuvant for cancer immunotherapies. As the presence of DCs within the tumor microenvironment promotes adaptive antitumor immunity, enhancement of DC migration toward the tumor microenvironment following DC vaccination might represent one possible approach to increase its therapeutic efficacy. While recent findings suggest the activity-regulated cytoskeleton-associated protein/activity-regulated gene 3.1 (Arc/Arg3.1) as critical regulator of DC migration in the context of autoimmune diseases, we aimed to investigate the impact of Arc/Arg3.1 expression for DC-based cancer vaccines. To this end, DC migration capacity as well as the induction of T cell-mediated antitumor immunity was assessed in an experimental B16 melanoma model with Arc/Arg3.1 −/- and Arc/Arg3.1 -expressing BMDCs applied as a subcutaneous vaccine. While antigen presentation on DCs was critical for unleashing effective T cell mediated antitumor immune responses, Arc/Arg3.1 expression enhanced DC migration toward the tumor and secondary lymphoid organs. Moreover, Arc/Arg3.1-expressing BMDCs shape the tumor immune microenvironment by facilitating tumor recruitment of antigen-specific effector T cells. Thus, Arc/Arg3.1 may represent a novel therapeutic target in DCs in order to increase the therapeutic efficacy of DC vaccination.